Formulations of NaOCl-based in liquid, gel form or with surfactants on dentin deproteinization before fiber post cementation - de Sousa Gomes Costa, Joatan Lucas [UNESP]; Barros, Antonia Patricia Oliveira [UNESP]; Manzoli, Tatiane Miranda [UNESP]; Escalante-Otárola, Wilfredo Gustavo; de Melo Alencar, Cristiane; Galvani, Lucas David [UNESP]; Vaz, Luis Geraldo [UNESP]; Kuga, Milton Carlos [UNESP] (Japanese Society for Dental Materials and Devices, 2024)
The objective of the study was to evaluate the effects of dentin deproteinization protocols for post space using different formulations containing sodium hypochlorite before fiber post cementation with self-adhesive resinous cement. The groups were divided according to the irrigation protocol (DWC, SHS, SHT and SHG). The residue cleanliness, bond strength, adhesive failure pattern, and tag formation at the adhesive interface between the self-adhesive cement and the dentin were evaluated. For this, analysis in scanning electron microscope, push-out test and confocal laser scanning microscopy were performed. The SHT protocol showed the highest residue cleanliness on the dentin surface of the post space (p<0.05). In addition, SHT protocol showed highest bond strength and tag formation in the cervical and middle thirds (p<0.05). Dentin deproteinization with sodium hypochlorite with surfactant provided the best dentin cleaning of residues, bond strength and tag formation after cementation of the fiber post with self-adhesive cement.
Keywords: Adhesion; Dentin; Post; Resin; Sodium hypochlorite